Problems of methodology of management of innovative development of the Мicroelectronic industry in no equilibrium conditions of economy - V. V. Ilyuk (Путеводитель предпринимателя)
In article problems and an order of formation of methodology of management are considered by groups of the knowledge-intensive enterprises, innovative clusters, at their modernization, rearmament. Methods of management and distributions of innovative products and release of a batch production are specified. Risks, elements and mechanisms, and order of use of the fixed and revolving funds for the purpose of maintenance and development of competitiveness of the organization are considered.